Hubungan Posisi Spinal Blok Anestesi Dengan Terjadinya Retensi Urine Pasca Anestesi Di Ruang IBS RSUD dr. H. Jusuf SK Provinsi Kalimantan Utara - Prayitno Prayitno; Happy Nurhayanti; Eko Puji Rahayu (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Background: Post spinal anesthesia complications, one of which is urinary retention, it is an inabity of the bladder to partially of completely empty urine during urination. In performing injections on the subarachnoid can be done on the patient in a sitting position on the surgery table or in a tilted/lateral decubitus position. Objective: To analyze the corellation between spinal position an the occurrence of post-anesthesia urinary retention, with the inclusion criteria of patients undergoing spinal block anesthesia in sitting position. Research Methods: The design of this research is analytical observation with a cross sectional approach, sampling using pusposive sampling technique. The number of samples as many as 42 people, the sample was taken in the Central Surgical Installation Room of RSUD dr. H. Jusuf SK. Collecting data using observation sheets that have been prepared and given instructions on how to fill them, regarding the patient’s sitting position in spinal surgery, that is the sitting position with both legs straight or sitting sitting position with both knees flexed, as well as the patient’s ability to urinate after spinal surgery, which is less than 8 hours or more than 8 hours after spinal surgery. From the study, the were 16 respondents who experienced post-spinal urinary retention, 13 respondents who received a spinal sitting position with both legs straight and 3 respondents who received a spinal sitting position with both knees flexed. Result: Statistical test using chi square, obtained P value = 0.715, thus P value > alpha (0.05), so Ho is accepted, it means that it can be concluded that there is no correllation between spinal anesthesia block position and the ccurance of post-anesthesia urinary retention.